(untitled) (Namibian Journal of Linguistics, Literature and Communication Studies, 2024)
The paper aimed at studying the challenges as well as the potential benefits associated with using African languages as the main medium of instructions in Namibian schools. Research indicates that there is more to gain in promoting African languages in all aspects of education and governance than the opposite. Countries that place greater emphasis on mother tongue instructions continue to thrive socially and economically. Countries such as China, Japan, South Korea, are some of the Asian countries who were once dominated by Europeans who opted for investing in their languages and are thriving economically. The results of the research indicates that the sole use of English language as the main medium of instruction in schools is the reason for high failure rates in grade 10 and 12 final examinations. Due to lack of enthusiasm from the government regarding the use of indigenous African languages as M.O.I , many teachers and students alike still prefer English to be the main medium of instruction in schools at the expense of their own languages. The government should revise its education policy on language instruction and put more emphasis on the need to robustly use indigenous African languages with English in all schools.